2021
DOI: 10.3310/hta25560
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive imaging software to assess the functional significance of coronary stenoses: a systematic review and economic evaluation

Abstract: Background QAngio® XA 3D/QFR® (three-dimensional/quantitative flow ratio) imaging software (Medis Medical Imaging Systems BV, Leiden, the Netherlands) and CAAS® vFFR® (vessel fractional flow reserve) imaging software (Pie Medical Imaging BV, Maastricht, the Netherlands) are non-invasive technologies to assess the functional significance of coronary stenoses, which can be alternatives to invasive fractional flow reserve assessment. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 154 publications
(441 reference statements)
0
6
0
Order By: Relevance
“…3 QFR has been extensively investigated and previous studies from China, Europe and Japan demonstrated both feasibility and accuracy of online QFR assessment. 4 A recent meta-analysis that included thirty-nine studies involving 5,440 patients observed that QFR had a good diagnostic accuracy to predict FFR<0.80, with a meta-analytic sensitivity and speci city of 85% and 91%, respectively. 4 Our results are supportive and incremental because we observed very similar diagnostic characteristics for QFR in our Latin-American population.…”
Section: Clinical Value Of Ffrmentioning
confidence: 99%
See 2 more Smart Citations
“…3 QFR has been extensively investigated and previous studies from China, Europe and Japan demonstrated both feasibility and accuracy of online QFR assessment. 4 A recent meta-analysis that included thirty-nine studies involving 5,440 patients observed that QFR had a good diagnostic accuracy to predict FFR<0.80, with a meta-analytic sensitivity and speci city of 85% and 91%, respectively. 4 Our results are supportive and incremental because we observed very similar diagnostic characteristics for QFR in our Latin-American population.…”
Section: Clinical Value Of Ffrmentioning
confidence: 99%
“…4 A recent meta-analysis that included thirty-nine studies involving 5,440 patients observed that QFR had a good diagnostic accuracy to predict FFR<0.80, with a meta-analytic sensitivity and speci city of 85% and 91%, respectively. 4 Our results are supportive and incremental because we observed very similar diagnostic characteristics for QFR in our Latin-American population. Very recently, the FAVOR II China (Angiographic quantitative ow ratio-guided coronary intervention) trial was published.…”
Section: Clinical Value Of Ffrmentioning
confidence: 99%
See 1 more Smart Citation
“…Vessel fractional flow reserve (vFFR) has been recently introduced into the armamentarium of catheterization laboratory practice aiming to simplify functional lesion assessment [ 5 , 16 ]. Its good correlation to invasive FFR, both in a pre- and post-PCI setting, was recently demonstrated [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its good correlation to invasive FFR, both in a pre- and post-PCI setting, was recently demonstrated [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. vFFR allows computation of FFR using a 3D reconstruction of coronary angiography without the necessity for a pressure wire or hyperemic agent [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%